Islam: the spirit of creativity: textbook proposal - Badi, Jamal Ahmed Bashier (2017)
The book titled “Islam and Creative Thinking” was a collection of academic articles relating to scholarly discussions about the multi-faceted aspects of creativity in the Islamic worldview. The new textbook proposal is to turn the abovementioned textbook into a student textbook.